Mixing with Impact Learning to Make Musical Choices - Oltheten, Wessel (Routledge, 2018)
"In Mixing with Impact: Learning to Make Musical Choices, Wessel Oltheten discusses the creative and technical concepts behind making a mix. Whether youre a dance producer in your home studio, a live mixer in a club, or an engineer in a big studio, the mindset is largely the same. The same goes for the questions you run into: where do you start? How do you deal with a context in which all the different parts affect each other? How do you avoid getting lost in technique? How do you direct your audiences attention? Why doesnt your mix sound as good as someone elses? How do you maintain your objectivity when you hear the same song a hundred times? How do your speakers affect your perception? Whats the difference between one compressor and another?Following a clear structure, this book covers these and many other questions, bringing you closer and closer to answering the most important question of all: how do you tell a story with sound?"--Provided by publisher